Puf3p, a Pumilio family RNA binding protein, localizes to mitochondria and regulates mitochondrial biogenesis and motility in budding yeast - García-Rodríguez, Luis J. (The Rockefeller University Press, 2007)
Puf3p binds preferentially to messenger RNAs (mRNAs) for nuclear-encoded mitochondrial proteins. We find that Puf3p localizes to the cytosolic face of the mitochondrial outer membrane. Overexpression of PUF3 results in reduced mitochondrial respiratory activity and reduced levels of Pet123p, a protein encoded by a Puf3p-binding mRNA. Puf3p levels are reduced during the diauxic shift and growth on a nonfermentable carbon source, conditions that stimulate mitochondrial biogenesis. These findings support a role for Puf3p in mitochondrial biogenesis through effects on mRNA interactions. In addition, Puf3p links the mitochore, a complex required for mitochondrial–cytoskeletal interactions, to the Arp2/3 complex, the force generator for actin-dependent, bud-directed mitochondrial movement. Puf3p, the mitochore, and the Arp2/3 complex coimmunoprecipitate and have two-hybrid interactions. Moreover, deletion of PUF3 results in reduced interaction between the mitochore and the Arp2/3 complex and defects in mitochondrial morphology and motility similar to those observed in Arp2/3 complex mutants. Thus, Puf3p is a mitochondrial protein that contributes to the biogenesis and motility of the organelle.